Assessing Knowledge and Predicting Grief Counseling Skills Among University Counseling Center Therapists. (April 2021) - Jankauskaite, Greta; O'Brien, Karen M.; Yang, NaYeon
This mixed-method study advances knowledge regarding the practice of grief counseling in a sample of 171 university counseling center therapists. First, several components of therapists' self-reported work with grieving clients was assessed (e.g., training level, initial responses to a grieving client, principles applied in counseling, therapist comfort, and potential therapist issues related to counseling grieving clients). Second, grounded in the death competence model (Gamino & Ritter, 2012), predictors of perceived grief counseling skills were examined. Cognitive competence and emotional competence predicted perceived grief counseling skills, with training/experience being the most robust predictor. Notably, the participants in this study rarely received education regarding death, dying, and grieving in their graduate programs, and they indicated that their knowledge about grief counseling was insufficient. Moreover, the therapists' qualitative responses to a case vignette were lacking in many grief-specific domains. Future directions for training, research, and clinical work are discussed.